Day 4 IFPRI Presentations for 2023 CGIAR GENDER-ICAR Conference - Nico, Gianluigi; Azzarri, Carlo; Ragasa, Catherine; Kyle, Jordan; Ma, Ning; Levy, Stephanie; Meinzen-Dick, Ruth S.; ElDidi, Hagar; Pereira, Audrey; Heckert, Jessica; Kosec, Katrina; Nchanji, Eileen; et al. (2023)
IFPRI is participating in the 2023 annual CGIAR Gender Research Conference. This conference is co-hosted by the CGIAR GENDER Impact Platform and the Indian Council of Agricultural Research (ICAR) and will take place in New Delhi, India, on October 9-12, 2023.